MANTRA PADA TRADISI MINUMAN PENGASIH DALAM PERNIKAHAN SUKU DAYAK BELUSU: KAJIAN FOLKLOR - Sulistriani, Jenny; Mursalim, Mursalim; Dahlan, Dahri (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
The formulation of the problem in this study are (1) what is the form of the mantra in the tradition of the Dayak Belusu wedding Minuman Pengasih? (2) what is the function of the mantra contained in the tradition of the Dayak Belusu tribe wedding Minuman Pengasih? The research objectives were (1) to describe the form of the mantra in the tradition of the Dayak Belusu Minuman Pengasih Â (2) to describe the function of the mantra contained in the tradition of the Dayak Belusu wedding Minuman Pengasih. The type of research used in this research is field research with a qualitative descriptive approach. The data used in this research is the mantra on the tradition of minuman pengasih in the Dayak Belusu tribal marriage, while the data sources in this study were obtained from informants. Data collection techniques used in this study include: observation, interviews, and documentation. The data analysis technique used in the research used qualitative analysis techniques, namely: (1) data collection, (2) data transcript, (3) transliteration, (4) drawing conclusions. The results of the analysis of the form of the mantra in the tradition of loving drink in Belusu tribal weddings are a form of prayer to the spirits of the ancestors and the function of the mantra to keep things away from bad things, so that the Belusu community events run smoothly and remain harmonious.